Accuracy of the highly sensitive C-reactive protein/albumin ratio to determine disease activity in inflammatory bowel disease. Issue 14 (9th April 2021) - Liu, Ailing; Lv, Hong; Tan, Bei; Shu, Huijun; Yang, Hong; Li, Ji; Qian, Jiaming
Abstract : Abstract: Persistent disease activity is associated with a poor prognosis in patients with inflammatory bowel disease (IBD). This study aims to explore the accuracy of the highly sensitive C-reactive protein/albumin ratio (CAR) in determining IBD activity. The clinical data of 231 IBD patients treated at Peking Union Medical College Hospital from 2012 to 2018 were analyzed retrospectively. The patients were classified as having active disease or remission according to the Crohn disease activity index scores for patients with Crohn disease (CD) and partial Mayo scores for patients with ulcerative colitis (UC). This study included 231 IBD patients (137 CD and 94 UC). From these groups, 182 patients had active disease, while 49 patients were in remission. The platelet counts, erythrocyte sedimentation rates, high-sensitivity C-reactive protein levels, and CAR scores were significantly higher, while hemoglobin levels, ALB, and body mass indexes were significantly lower in patients with active disease ( P  < 0.01). The hsCRP, CAR, and ALB significantly correlated with disease activity for both CD and UC ( P  < 0.001). The area under the curve (AUC) of CAR was highest among the laboratory indexes at 0.829, and the AUC of CAR in the UC patients was larger than that of the CD patients. Also, CAR with cutoff value of 0.06 displayed the highest sensitivity among the indexes for IBD activity at 83.05%. CAR is a useful biomarker for identifying disease activity in patients with CD and UC. Higher CAR levels are indicative of increased IBD activity. CAR may be more valuable in UC than that in CD for assessing the degree of IBD activity.